Iraq's Future : The Aftermath of Regime Change - Dodge, Toby (London ; New York Routledge for the International Institute for Strategic Studies, 2005)
'Iraq's Future' investigates the difficult and costly regime change in Baghdad, taking into account US troops, the new Iraqi government and the future of state-building. The book describes what is involved in building a new government from scratch.
Include Notes.
Keywords: Iraq -- Politics and government -- Forecasting